Indonesia's Role in the ASEAN Indo-Pacific Forum - Lailatul Lufiah; Halifa Haqqi; Untari Narulita Madyar Dewi (International Journal of Scientific Multidisciplinary Research, 2024)
This research aims to look at Indonesia's role in the establishment of the ASEAN Indo-Pacific Forum (AIPF) and Indonesia's interests in AIPF. Researchers used role theory and the concept of national interest to carry out the analysis. Then the method used by the author is a descriptive qualitative method. Primary data was obtained directly by the author through a visit to the Coordinating Ministry for Political, Legal and Security Affairs (KemenkoPolhukam) in October 2023, then researchers also used government and international statements to strengthen the research results. The result of this research is Indonesia's success in implementing one of the pillars of the ASEAN Outlook Out the Indo-Pacific (AOIP), namely Indo-Pacific prosperity through inclusive and open cooperative dialogue in the fields of economics, connectivity and sustainable development through a forum formed under the name AIPF (ASEAN Indo-Pacific Forum). The birth of AIPF for Indonesia is an economic improvement through investment received by Indonesia and makes Indonesia's position stronger in international eyes